An Alcohol Dehydrogenase 3 (ADH3) from Entamoeba histolytica Is Involved in the Detoxification of Toxic Aldehydes - Constantin König; Martin Meyer; Corinna Lender; Sarah Nehls; Tina Wallaschkowski; Tobias Holm; Thorben Matthies; Dirk Lercher; Jenny Matthiesen; Helena Fehling; Thomas Roeder; Sophia Reindl; et al. (Microorganisms, 2020)
Recently, a putative alcohol dehydrogenase 3, termed EhADH3B of the Entamoeba histolytica isolate HM-1:IMSS was identified, which is expressed at higher levels in non-pathogenic than in pathogenic amoebae and whose overexpression reduces the virulence of pathogenic amoebae. In an in silico analysis performed in this study, we assigned EhADH3B to a four-member ADH3 family, with ehadh3b present as a duplicate (ehadh3ba/ehadh3bb). In long-term laboratory cultures a mutation was identified at position 496 of ehadh3ba, which codes for a stop codon, which was not the case for amoebae isolated from human stool samples. When using transfectants that overexpress or silence ehadh3bb, we found no or little effect on growth, size, erythrophagocytosis, motility, hemolytic or cysteine peptidase activity. Biochemical characterization of the recombinant EhADH3Bb revealed that this protein forms a dimer containing Ni2+ or Zn2+ as a co-factor and that the enzyme converts acetaldehyde and formaldehyde in the presence of NADPH. A catalytic activity based on alcohols as substrates was not detected. Based on the results, we postulate that EhADH3Bb can reduce free acetaldehyde released by hydrolysis from bifunctional acetaldehyde/alcohol dehydrogenase-bound thiohemiacetal and that it is involved in detoxification of toxic aldehydes produced by the host or the gut microbiota.